Analysis of the Pidgin Language on Dat Stick by Rich Brian - Shoufi Nisma Dewi (CV. Rayyan Dwi Bharata, 2023)
Pidgin dialects are at risk for vanishing because of the impact of urbanization, globalization, and the strength of significant world dialects. The shift in language, migration, and the disappearance of traditional cultural practices all make it even more challenging to preserve and maintain pidgin languages. It is necessary to acknowledge the preservation of linguistic diversity, including pidgin languages, which are important for intergroup communication and represent distinct cultural identities. The examination philosophy utilized in this study includes a blend of information assortment from